The Role of Spatial Planning Audit in Law Enforcement - Myrna A. Safitri (IHSA Institute, 2024)
Spatial planning plays an essential role in disaster prevention because it can ensure the proper distribution of land use in accordance with the environment's carrying capacity. Uncontrolled land use has the potential to cause disasters in addition to the problems of environmental damage and pollution. Spatial audit in Indonesian law is one of the instruments used to implement spatial use control. Audit results can be used to support law enforcement. This article discusses how spatial audit can have a role in supporting law enforcement processes that are based on more comprehensive scientific data and analysis. This article results from dogmatic legal research based on data and analysis of Indonesian spatial legal norms. This research found that spatial audits need to be optimally implemented. In general, audits are conducted in response to public compliance, in the event of a disaster, or when the spatial plan is revised. In the future, it is recommended that audits be conducted regularly to support the effectiveness of spatial use control